CASE STUDY: IMPLEMENTATION OF P5 ON SCHOOL CULTURE, NUMERATION LITERACY AND CHILDREN'S CHARACTER FORMATION AT SDN 1 BUG-BUG - Herjan Haryadi; Laili Saadah; Trisna Kusuma Wardani (Universitas Islam Negeri Mataram, 2025)
The Pancasila Student Profile Strengthening Project (P5) is a learning approach that emphasizes the development of student character and competencies aligned with Pancasila values, providing contextual, collaborative, and problem-solving-oriented learning experiences that enable students to develop strong character. The purpose of this study is to investigate the impact of implementing the Pancasila student profile strengthening project on school culture, mathematical numeracy literacy, and character building in elementary school. The research method employed is a case study approach. The research techniques used are interviews, observation, and documentation. The data analysis employed in this study involves data reduction, data display, and data verification. At the same time, the validity of the data in this study is ensured through triangulation, researcher persistence, and the extension of the study period. The research results obtained indicate that the implementation of P5 was carried out independently by teachers of elementary school, without any training project to strengthen the profile of Pancasila students. Low problem-solving skills in numeracy literacy among students are addressed through collaborative methods, which include learning mathematical numeracy literacy in the context of memorization, congregational prayer activities in turns, reading the Yasin letter every Friday, cooperation in cleaning, planting flowers, and farming. The supporting factors include teachers and students, while the inhibiting factors are a lack of government support, a lack of in-depth knowledge of the independent learning curriculum or P5, limited time allocation, low student engagement, insufficient parental attention, and an unfavorable environment